Étude comparative entre les deux systèmes de déshydratation (par glycol/ par les échangeurs de chaleur) du gaz Lift en tête de puits au niveau de la région de TFT - إسماعيل, حنكة; جمال الدين, بقاط; رياض, عموشي (University of El-Oued, 2020)
"When the energy of the reservoir is too low for the well to eruptive, or when the desired production rate is greater than that possible with the energy of the reservoir. It becomes necessary to set up a means of activation. The exploitation of the TFT field by natural depletion has dropped its reservoir pressure considerably, so they opted for pressure maintenance with the injection of gas lift, but in winter when temperatures reach 8 °C, and due to the presence of water and some impurities, the gas lift freezes under specific conditions at the level of the injection pipes, To avoid the problem of hydrate formation in the gas lift. The first method is the injection of di-ethylene glycol before the CAMCO valve, which makes it possible to dehydrate the gas lift by lowering the temperature by inhibiting the formation of hydrates, and the second is the installation of a heat insulator at the wellhead, the aim is to obtain the recovery of a certain quantity of heat under optimal economic conditions which are in compromise between the investment costs and the operating costs." "عندما تكون طاقة الخزان منخفضة للغاية بحيث لا يمكن للبئر أن تنفجر ، أو عندما يكون معدل الإنتاج المطلوب أكبر من ذلك الممكن مع طاقة الخزان. يصبح من الضروري إنشاء وسيلة التنشيط. أدى استغلال حقل TFT عن طريق النضوب الطبيعي إلى خفض ضغط خزانه بشكل كبير ، لذلك اختاروا الحفاظ على الضغط بحقن رفع الغاز ، ولكن في الشتاء عندما تصل درجات الحرارة إلى 8 درجات مئوية ، وبسبب وجود الماء وبعض الشوائب ، يتجمد رفع الغاز في ظل ظروف محددة على مستوى أنابيب الحقن ، لتجنب مشكلة تكوين الهيدرات في المصعد الغازي. الطريقة الأولى هي حقن ثنائي إيثيلين جلايكول قبل صمام كامكو ، مما يجعل من الممكن تجفيف الرافعة الغازية عن طريق خفض درجة الحرارة عن طريق تثبيط تكوين الهيدرات ، والثاني هو تركيب عازل حراري عند فوهة البئر ، الهدف هو الحصول على استرداد كمية معينة من الحرارة في ظل الظروف الاقتصادية المثلى التي تكون في وسط بين تكاليف الاستثمار وتكاليف التشغيل. "
Génie chimiqueمذكرة ماستر تخصص
Keywords: Hydrates; Gas lift; Di-ethylene glycol; heat insulator, eruptive.; هيدرات؛ رفع الغاز ثنائي اثيلين غلايغول؛ عازل للحرارة ، ثوراني.